Prognostic role of Twist or Snail in various carcinomas: a systematic review and meta‐analysis. (November 2014) - Zhang, Ping; Hu, Pingping; Shen, Hongchang; Yu, Jianyu; Liu, Qi; Du, Jiajun
Abstract Background Twist and Snail are considered as key transcriptional repressors of E‐cadherin tightly related to epithelial‐to‐mesenchymal transition (EMT) and cancer progression. Numerous studies have investigated the prognostic value of Twist and Snail. However, the published results were controversial or even opposite. Our article aimed to evaluate the prognostic role of Twist and Snail in patients with cancer. Design A comprehensive literature search of PubMed, Embase and Web of Science was conducted. Pooled hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were assessed to quantify the prognostic role. Results The pooled HR with 38 studies for Twist was 2·18 (95% CI: 1·77–2·68, I2 = 69·8%, P = 0·000) and for Snail with 40 studies was 1·58 (95% CI: 1·33–1·87, I2 = 70·0%, P = 0·000), suggesting high Twist/Snail expression predicted poor prognosis related to all clinical outcomes. For Twist, the pooled HR for overall survival (OS) was 2·07 (95% CI: 1·63–2·63, I2 = 72·6%, P = 0·000) and for progression‐free/recurrence‐free/metastasis‐free/disease‐free/cancer‐free survival (PFS/RFS/MFS/DFS/CFS) was 2·36 (95% CI: 1·76–3·17, I2 = 65·0%, P = 0·000). For Snail, the pooled HR for OS was 1·63 (95% CI: 1·33–1·99, I2 = 70·8%, P = 0·000) and for PFS/RFS/MFS/DFS/CFS was 1·54 (95% CI: 1·17–2·02, I2 = 59·1%, P = 0·001). All of those results were suggesting that high Twist/Snail expression was associated with poor prognosis. Furthermore, when grouped into different types of cancers, the pooled HRs were also calculated for the subgroups. No publication bias was found except studies evaluating all clinical outcomes of Twist (P = 0·006 for Begg's test and 0·006 for Egger's test). Conclusions Elevated Twist or Snail expression in tumour tissue indicated poor prognosis for cancer.